PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN TEAMWORK TERHADAP TINGKAT KEPUASAN KERJA GURU DI SMPS DELI MURNI BANDAR BARU: PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN TEAMWORK TERHADAP TINGKAT KEPUASAN KERJA GURU DI SMPS DELI MURNI BANDAR BARU - Ginggar, Benediktus Sipandi; Rahman , Arif; Arnelly, Arnelly (Manajer Pendididikan, 2025)
Research was conducted to analyze the influence of academic supervision and teamwork on the level of teacher job satisfaction at SMPS Deli Murni Bandar Baru. The research sample was 50 teachers using the total sample. Data collection uses a questionnaire. The data analysis technique uses statistical correlation tests using Pearson product moment analysis and regression tests. The research results show that: (1) There is a positive relationship between academic supervision and teacher job satisfaction. (2) There is a positive relationship between teamwork and teacher job satisfaction. (3) There is a joint relationship between academic supervision and teamwork with teacher job satisfaction of 52% at SMPS Deli Murni Bandar Baru